Proton cyclotron wave generation mechanisms upstream of Venus - Delva, M. (2011)
[1] Long-term observations of proton cyclotron waves in the upstream region of Venus raise the question of under which general solar wind conditions these waves are generated and maintained. The waves are characterized by their occurrence at the local proton cyclotron frequency and left-hand polarization, both in the spacecraft frame. Magnetometer data of the Venus Express spacecraft for two Venus years of observations are analyzed before, during, and after the occurrence of these waves. The configuration of the upstream magnetic field and the solar wind velocity is investigated, to study if the waves are generated from a ring distribution of pickup ions in velocity space or from a parallel pickup ion beam, i.e., for quasi-parallel conditions of solar wind velocity and magnetic field when the solar wind motional electric field is weak. It is found that stable and mainly quasi-parallel magnetic field conditions for up to ∼20 min prior to wave observation are present, enabling sufficient ion pickup and wave growth to obtain observable waves in the magnetometer data. Persistent waves occur mainly under quasi-parallel conditions. This is in agreement with linear theory, which predicts efficient wave growth for instabilities driven by field-aligned planetary ion beams, already for low pickup ion density. The occurrence of highly coherent waves at 4 RV upstream toward the Sun implies that planetary neutral hydrogen is initially picked up at least 5 RV toward the Sun from a sufficiently dense Venus hydrogen exosphere.